Prediction of Gastric Cancer-Related Genes Based on the Graph Transformer Network - Chen, Yan; Sun, Xuan; Yang, Jiaxing (Frontiers in Oncology, 2022)
Gastric cancer is a complex multifactorial and multistage process which involves a large number of tumor-related gene structural changes and abnormal expression. Therefore, knowing the related genes of gastric cancer can further understand the pathogenesis of gastric cancer and provide guidance for the development of targeted drugs. Traditional methods to discover gastric cancer-related genes based on biological experiments are time-consuming and expensive. In recent years, a large number of computational methods have been developed to identify gastric cancer-related genes. In addition, a large number of experiments show that establishing a biological network to identify disease-related genes has higher accuracy than ordinary methods. However, most of the current computing methods focus on the processing of homogeneous networks, and do not have the ability to encode heterogeneous networks. In this paper, we built a heterogeneous network by disease similarity network and gene interaction network. We implemented graph transformer network(GTN) to encode this heterogeneous network. In the meanwhile, deep belief network(DBN) was applied to reduce the dimension of feature. We call this method ‘DBN-GTN’ and it performed best among four traditional methods and five similar methods.